Recommendations on the structure, personal, and organization of intensive care units - Waydhas, Christian; Riessen, Reimer; Markewitz, Andreas; Hoffmann, Florian; Frey, Lorenz; Böttiger, Bernd W.; Brenner, Sebastian; Brenner, Thorsten; Deffner, Teresa; Deininger, Matthias M.; Janssens, Uwe; Kluge, Stefan; et al. (Frontiers in Medicine, 2023)
Background: Intensive care units (ICU) are central facilities of medical care in hospitals world-wide and pose a significant financial burden on the health care system. Objectives: To provide guidance and recommendations for the requirements of (infra)structure, personal, and organization of intensive care units. Design and Setting: Development of recommendations based on a systematic literature search and a formal consensus process from a group of multidisciplinary and multiprofessional specialists from the German Interdisciplinary Association of Intensive Care and Emergency Medicine (DIVI). The grading of the recommendation follows the report from an American College of Chest Physicians Task Force. Results: The recommendations cover the fields of a 3-staged level of intensive care units, a 3-staged level of care with respect to severity of illness, qualitative and quantitative requirements of physicians and nurses as well as staffing with physiotherapists, pharmacists, psychologists, palliative medicine and other specialists, all adapted to the 3 levels of ICUs. Furthermore, proposals concerning the equipment and the construction of ICUs are supplied. Conclusion: This document provides a detailed framework for organizing and planning the operation and construction/renovation of ICUs.